Determination of the relative influences of carbon doping and disorder on field and temperature dependent critical current density of MgB2 - Chen, Soo Kien; Xu, Xun; Kim, Jung Ho; Dou, Shi Xue; MacManus-Driscoll, Judith Louise (Institute of Physics Publishing, 2009)
SiC was mixed with Mg and B and reacted by either a one-step in situ or two-step method at 650 or 850 °C. By doing so, it was possible to determine the extent to which scattering via C doping influences the magnitude of field dependent critical current density, Jc(H), compared to pinning via generation of microstructural disorder. The one-step reaction method leads to Mg2Si formation and at the same time to more C doping of MgB2 than the two-step method. Carbon increases both the irreversibility field, Hirr, and upper critical field, Hc2 (T<28 K). However, for the temperatures (6 and 20 K) and fields (up to 7 T) studied, pinning rather than scattering overwhelmingly dominates the magnitude of the field dependent critical current density.